2014
DOI: 10.1186/2051-4190-24-8
|View full text |Cite
|
Sign up to set email alerts
|

Precocious initiation of spermatogenesis in a 19-month-old boy with Hurler syndrome

Abstract: Mucopolysaccharidosis type IH (MPS IH) is a rare autosomal recessive lysosomal storage disorder. Haematopoietic stem cell transplantation (HSCT) has been proposed for the treatment of MPS IH patients and offers the possibility to grow into their adulthood. Precocious puberty has been described in few MPS patients. We report, to the best of our knowledge and for the first time, the initiation of the first waves of spermatogenesis fortuitously observed in seminiferous tubules of a pre-pubertal 19-month-old boy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Vimentin and Anti-Müllerian hormone for Sertoli cells; Androgen Receptor for Sertoli and Leydig cells; 3β-Hydroxysteroid dehydrogenase for Leydig cells) were maintained in human (pre)pubertal testicular tissue after thawing according to expected expression related to patient age, confirming the ability of our CSF to also preserve somatic cells after thawing. 42 However, it should be noted that PCNA expression was not detected in spermatogonia of several (pre)pubertal patients, both in fresh and frozen-thawed tissue, thus causing potential bias in interpretation of our data. Several hypotheses can be put forward to explain the absence of PCNA expression in spermatogonia and Sertoli cells: (i) loss of cellular proliferative capacity, (ii) lack of DNA repair expression induced by cryodamage, (iii) loss by necrosis of cells theoretically able of expressing PCNA.…”
Section: Discussionmentioning
confidence: 77%
“…Vimentin and Anti-Müllerian hormone for Sertoli cells; Androgen Receptor for Sertoli and Leydig cells; 3β-Hydroxysteroid dehydrogenase for Leydig cells) were maintained in human (pre)pubertal testicular tissue after thawing according to expected expression related to patient age, confirming the ability of our CSF to also preserve somatic cells after thawing. 42 However, it should be noted that PCNA expression was not detected in spermatogonia of several (pre)pubertal patients, both in fresh and frozen-thawed tissue, thus causing potential bias in interpretation of our data. Several hypotheses can be put forward to explain the absence of PCNA expression in spermatogonia and Sertoli cells: (i) loss of cellular proliferative capacity, (ii) lack of DNA repair expression induced by cryodamage, (iii) loss by necrosis of cells theoretically able of expressing PCNA.…”
Section: Discussionmentioning
confidence: 77%
“…The increase in AR expression happens in a testosterone-free environment, thus not inducing Sertoli cell maturation. If due to abnormal conditions, testosterone production is maintained during the expectedly “quiescent” period, AMH expression is inhibited, reflecting precocious Sertoli cell maturation [48,49].…”
Section: Sertoli Cell Maturation During Postnatal Developmentmentioning
confidence: 99%
“…As previously mentioned, the decrease in AMH expression at pubertal onset is indicative of Sertoli cell maturation. Despite the fact that AMH downregulation by androgens has been established a long time ago in all animals studied, including human [55,58,96,142], mouse [8,48,49,143], ram [144,145], pig [146,147], stallion [148], bovine [149,150], and tammar wallaby [151], it has not been until recently that the underlying mechanism of androgen action was described [30].…”
Section: Androgens and The Sertoli Cellmentioning
confidence: 99%
“…Another case report with MPS I revealed that ERT was safe for the mother during pregnancy and for her baby ( Castorina et al, 2015 ), while four successful pregnancies were described in MPS I women treated by bone marrow transplantation ( Rémerand et al, 2009 ). On the other hand, signs of precocious puberty were detected in some boys affected with MPS I and MPS III ( Milazzo et al, 2014 ) and MPS III A (Tylki-Szymanska & Metera).…”
Section: Introductionmentioning
confidence: 99%